Analisis Keterampilan Guru dalam Mengadakan Variasi Metode Pembelajaran di Kelas III Sekolah Dasar - Detania Hidapenta; Fira Ayu Dwiputri; Fitri Nur Aulia Kurniawati; Natasya Febriyanti; Sania Amaliyah (Journal on Education, 2023)
This research is motivated by the facts found in the field that there are still many teachers who do not master teaching skills, especially skills in carrying out a variety of learning methods, so the researcher intends to discuss teacher problems or obstacles in carrying out various methods in teaching and learning activities and what efforts teachers can make in conducted a variety of methods in elementary schools, especially grade 3. Based on the research that had been conducted by the researchers through a qualitative descriptive research method with the research subject being class III teachers at SDN A and class V teachers at SDN B in Bandung City, various teacher problems were found in carrying out variations on learning methods. These obstacles are: (1) not all students can follow the teacher's learning strategies and methods; (2) the teacher's busyness in several activities; (3) the teacher's lack of knowledge regarding the selection of appropriate methods and strategies for students; (4) as well as the lack of facilities and infrastructure in schools.